Impact of workers’ welfare after MSPO implementation / Nurul Nabilah Mohyidin and Syahrizan Syahlan - Mohyidin, Nurul Nabilah; Syahlan, Syahrizan (Faculty of Plantation and Agrotechnology, 2018)
Sustainable palm oil is an approach to oil palm agriculture that aims to produce palm oil without causing deforestation or harming people. The Malaysian Sustainable Palm Oil (MSPO) standard has been made mandatory by the end 2019. In the context of palm oil sustainability, the similar type of scheme been implemented are Roundtable Sustainable Palm Oil (RSPO) and Indonesia Sustainable Palm Oil (ISPO). Most of the research on MSPO implementation are focus more on awareness and factors but a very lack of study was conducted to identify the impact of MSPO. This study is to identify the impacts of worker’s welfare after MSPO implementation. This study covers knowledge, perceived benefits and government support as independent variables. A total 52 respondents were at Syarikat Perladangan Peserta Kundang Ulu, Tangkak, Johor. All the variables are positive relationship. In addition, knowledge (0.730) shows a very strong relationship towards the dependent variable. The results shows that the R² is 0.610 which indicate that 61% of the independent variables have been identified in this study. However, result of regression shows that there is no significant relationship between government support and the impacts of MSPO. Hence, it can be concluded that the most dominant impact of workers’ welfare after MSPO implementation is knowledge. From these three impacts, perceived benefits and knowledge gave influence towards worker’s welfare after MSPO implementation.